Extracellular Matrix Proteins Confer Cell Adhesion-Mediated Drug Resistance Through Integrin αv in Glioblastoma Cells - Yu, Qi; Xiao, Weikun; Sun, Songping; Sohrabi, Alireza; Liang, Jesse; Seidlits, Stephanie K. (Frontiers in Cell and Developmental Biology, 2021)
Chemotherapy resistance to glioblastoma (GBM) remains an obstacle that is difficult to overcome, leading to poor prognosis of GBM patients. Many previous studies have focused on resistance mechanisms intrinsic to cancer cells, the microenvironment surrounding tumor cells has been found more recently to have significant impacts on the response to chemotherapeutic agents. Extracellular matrix (ECM) proteins may confer cell adhesion-mediated drug resistance (CAMDR). Here, expression of the ECM proteins laminin, vitronectin and fibronectin was assessed in clinical GBM tumors using immunohistochemistry. Then, patient-derived GBM cells grown in monolayers on pre-coated laminin, vitronectin, or fibronectin substrates were treated with cilengitide, an integrin inhibitor, and/or carmustine, an alkylating chemotherapy. Cell adhesion and viability were quantified. Transcription factor (TF) activities were assessed over time using a bioluminescent assay in which GBM cells were transduced with lentiviruses containing consensus binding sites for specific TFs linked to expression a firefly luciferase reporter. Apoptosis, mediated by p53, was analyzed by Western blotting and immunocytofluoresence. Integrin αv activation of the FAK/paxillin/AKT signaling pathway and effects on expression of the proliferative marker Ki67 were investigated. To assess effects of integrin αv activation of AKT and ERK pathways, which are typically deregulated in GBM, and expression of epithelial growth factor receptor (EGFR), which is amplified and/or mutated in many GBM tumors, was assessed using shRNA knockdown. Laminin, vitronectin and fibronectin were abundant in clinical GBM tumors and promoted CAMDR in GBM cells cultured on pre-coated substrates. Cilengitide treatment induced cell detachment, which was most pronounced for cells cultured on vitronectin. Cilengitide treatment, increased cytotoxicity of carmustine, reversing CAMDR. ECM adhesion increased activity of NFκB and decreased that of p53 leading to suppression of p53-mediated apoptosis and upregulation of multi-drug resistance gene 1 (MDR1). Expression of Ki67 was correlative with activation of the integrin αv-mediated FAK/Paxillin/AKT signaling pathway. EGFR expression increased with integrin αv knockdown GBM cells and may represent a compensatory survival mechanism. These results indicate extracellular matrix proteins confer cell adhesion-mediated drug resistance through integrin αv in glioblastoma cells.